IMPLEMENTASI MANAJEMEN KURIKULUM PADA MADRASAH DINIYAH AL-AZIZ PONDOK PESANTREN NURUL BUDA II KABUPATEN SLEMAN D.I. YOGYAKARTA - Ali Khudrin (Analisa: Journal of Social Science and Religion, 2008)
This research was done at Madrasah Diniyah Al Aziz which locatedat Nurul Huda II Islamic Boarding School, Sleman Regency, D.I.Yogyakarta with the implementation of the management of curriculumas the focus of the research. The result of this research showed that theimplementation of the management of curriculum which applied toMadrasah Diniyah Al Aziz was in accordance with principles of management, namely first the curriculum was planned thoroughly by thecurriculum team which consisted of the elements of the Foundation,Head of Madrasah Diniyah, Deputy Head of Curriculum Field, and someteachers. Unfortunately, the aspect of organizing curriculum was onlylimited to the division of components of activities by job description. Similarly, the implementation of the curriculum was still simple andonly orientated towards Islamic yellow books as what have been taughtat Nurul Huda II Islamic Boarding School as salaf Islamic BoardingSchool. Similarly, sorogan and bandongan systems have been used asthe teaching method. However, in general the curriculum practiced inthe learning process actually did not differ widely from the curriculumat madrasah diniyah which has existed in society, namely it was onlybased on books and religious books in accordance with grades.